Pengaruh Profitabilitas, Financial Distress, Firm Size Terhadap Audit Report Lag - Caroline Wibawa Tantianty (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
Recording and publication of financial reports to the public is something that must be done by companies going public. Timely publication can maintain the relevance and reliability of information in financial reports, so that it can be useful in making decisions. Companies in Indonesia still have problems publishing financial reports in a timely manner, delays in publication occur due to audit report lag, which is the time for public accountants to carry out the audit process from closing books to publication of financial reports. The population of this study are mining companies listed on the Indonesia Stock Exchange in 2020-2021. Data analysis in this research is descriptive statistical test, classic assumption test, multiple regression analysis, hypothesis testing, and coefficient of determination test. The results of the study stated that profitability had no effect on audit report lag, while company size and financial distress had an effect on audit report lag.